Método QuEChERS para determinação de ocratoxina a e citrinina em arroz e farelo de arroz - Hackbart, Helen Cristina dos Santos (2012)
THE QuEChERS METHOD FOR DETERMINATION OF OCHRATOXIN A AND CITRININ IN RICE AND RICE BRAN. The present study was carried out to establish the optimal conditions for performing ochratoxin A (OTA) and citrinin (CIT) extraction using the QuEChERS method in rice. Employing the factorial experimental design, variables that significantly influenced the extraction stages were determined. The following variables were analyzed: addition of water, acidification of acetonitrile with glacial acetic acid, as well as amounts of magnesium sulfate, sodium acetate, sodium citrate and diatomaceous earth. The best combining procedure resulted in a predictive model using more water and less diatomaceous earth. Recoveries of CIT and OTA were 78-105%.